GENES RESPONSIBLE FOR HEAVY METAL BIOACCUMULATION IN FUNGI ASPERGILLUS - Badr, Sanaa Qasem (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Heavy metal contamination, particularly with cadmium (Cd²⁺), lead (Pb²⁺), and arsenic (As³⁺/As⁵⁺), represents a critical environmental and health concern due to their toxicity and persistence. Microorganisms such as Aspergillus species have demonstrated significant potential for bioremediation, primarily through complex genetic and biochemical mechanisms. This study synthesizes existing literature to examine the molecular basis of heavy metal tolerance and bioaccumulation in Aspergillus. Method: This study synthesizes existing literature to examine the molecular basis of heavy metal tolerance and bioaccumulation in Aspergillus. Results: The findings highlight multiple defense strategies, including cadmium detoxification via glutathione biosynthesis genes (GSH1, GSH2), phytochelatin synthase (PCS), and vacuolar sequestration mediated by CDF transporters (CrpA, ZRC1, COT1). Lead bioaccumulation involves structural binding to cell wall polymers such as chitin, glucans, and melanin, complemented by transporter genes (CrpA, YCF1, ABC transporters) and intracellular chelation through glutathione and metallothioneins. Arsenic tolerance relies on aquaglyceroporin channels (Fps1), efflux transporters (Acr3), and arsenate reductase (ArsC), which enable reduction and detoxification, alongside phytochelatin-mediated sequestration. Across all metals, oxidative stress is mitigated by antioxidant defense genes, including SOD, CAT, and TRX, while Yap1-like transcription factors coordinate regulatory responses. Novelty: The integration of adsorption, chelation, transport, and oxidative stress defense establishes Aspergillus as a versatile and resilient organism capable of surviving in heavy metal-polluted environments. These findings underscore the potential application of Aspergillus in bioremediation strategies targeting multi-metal contamination.